2015
DOI: 10.1142/s1793545815500194
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy for detection of imatinib in plasma: A proof of concept

Abstract: Imatinib is the standard first line treatment for chronic myeloid leukemia (CML). Owing to dose-related toxicities of Imatinib such as neutropenia, there is scope for treatment optimization through therapeutic drug monitoring (TDM). Trough concentration of 1 μg/mL is considered the therapeutic threshhold. Existing methods for the detection of Imatinib in plasma are limited by long read out time and expensive instrumentation. Hence, Raman spectroscopy was explored as a rapid and objective tool for monitoring Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…In fact, only one example of the application to real clinical samples (i.e., serum of patients treated with mitoxantrone) has been published, and SERS showed an analytical performance comparable to HPLC [ 45 ]. Other drugs for which TDM is deemed relevant have been successfully quantified only in spiked biofluids (6-mercaptopurine [ 69 ], doxorubicin [ 70 ], imatinib [ 71 ], methotrexate [ 54 ], mitoxantrone [ 45 ], and paclitaxel [ 72 ]). All of the other studies considered buffered solutions of drugs, sometimes in the presence of serum proteins such as HSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, only one example of the application to real clinical samples (i.e., serum of patients treated with mitoxantrone) has been published, and SERS showed an analytical performance comparable to HPLC [ 45 ]. Other drugs for which TDM is deemed relevant have been successfully quantified only in spiked biofluids (6-mercaptopurine [ 69 ], doxorubicin [ 70 ], imatinib [ 71 ], methotrexate [ 54 ], mitoxantrone [ 45 ], and paclitaxel [ 72 ]). All of the other studies considered buffered solutions of drugs, sometimes in the presence of serum proteins such as HSA.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib, another anti-cancer drug for which TDM is deemed useful, was successfully determined at concentrations of 0.1, 0.005, and 0.001 mg/mL (2 × 10 −6 M–2 × 10 −4 M) in plasma [ 71 ], using gold nanoparticles deposited on aluminum-covered glass slides as SERS substrates. This study was considered by the authors themselves as a “proof of concept”, and did not provide any calibration or other figures of merit (e.g., LOD, LOQ, etc.…”
Section: Applications Of Sers Relevant To Tdmmentioning
confidence: 99%
“…As this paper is concerned with IMT detection in plasma, it is noteworthy that the SERS bands appearing at 988, 1032, 1307, and 1606 cm −1 in the spectrum of IMT in MeOH/Zn 2+ solution (Figure 2C), can be easily distinguished also in the SERS spectra of IMT in plasma (Figure 2B); indeed the Raman and SERS bands observed for the IMT were consistent with those reported in literature. 14,46 In other words, after a deproteinization step, SERS can successfully detect IMT in plasma. Most likely, IMT bands are readily observed in deproteinized plasma because the concentration of "free", unbound IMT, which is available for a direct interaction with the metal surface of the SERS substrate, is much higher than that present in whole plasma.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…13 Rath et al reported a proof of concept for the detection, but not for quantification, of IMT in human plasma at concentration of 1.7 μM (839 ng/ mL) and above with SERS. 14 However, SERS approaches quantifying IMT directly in plasma or other complex biofluids have not been reported yet. In this work, we present a spectroscopy-based point-of-care approach for a fast and inexpensive determination of IMT, thus offering to medical doctors an affordable protocol for dosing IMT.…”
mentioning
confidence: 99%
See 1 more Smart Citation